2019–2020 Florida Citrus Production Guide: Plant Bugs, Chewing Insect Pests, Caribbean Fruit Fly, and Thrips - Xavier Martini; Lauren M. Diepenbrock (EDIS, 2019)
This 5-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. The insects listed in this section are generalist feeders for which citrus is not a preferred host. They are, therefore, only sporadic problems in Florida citrus. While these pests do not require routine treatment in all groves, periodic outbreaks can potentially have dramatic impact on tree health and/or productivity. When these insects are detected at a damaging level, treatment is required. Written by Xavier Martini and Lauren M. Diepenbrock, and published by the Entomology and Nematology Department, March 2019.